Groundwater Pumping Options in Coastal Areas of Odisha - SETHI, RANU RANI; KALEDHONKAR, M. J.; DAS, M.; SRIVASTAVA, S. K.; NAYAK, A. K.; KUMAR, A. (Journal of the Indian Society of Coastal Agricultural Research, 2023)
Odisha has a long coast line stretching over 480 km in length along the eastern boundary of Bay of Bengal. These areas are highly sensitive in terms of saline water intrusion due to excessive groundwater pumping to meet the water requirement of increasing population and crop water demand. It is necessary that safe pumping options should be strictly followed to maintain sustainable groundwater withdrawal. This papers deals with estimation of optimal pumping options in two coastal districts of Odisha, i.e. Kendrapara and Jagatsinghpur, that occupies 2nd and 4th highest position in terms of groundwater development status within the State. Field studies were carried out to characterize the groundwater table depth fluctuation, change in water quality, aquifer properties, and specific capacity of the study area. Pumping test results in the study area showed that transmissivity value of aquifer ranged within 68.2 to 786.8 m2 day-1. Groundwater quality within the shallow aquifer was within the permissible limit of irrigation use. Due to presence of good aquifer zones and source of groundwater recharge, groundwater can be exploited safely in these areas. An analytical approach by using the Ghyben-Herzberg model has been used to calculate the total fresh water flow towards sea, safe pumping depth, well density, pumping mode within the study area. The model result indicated that even though both districts are sensitive to salinity, depth of pumping should be restricted within 6- 9.5m and 16 to 24.5m in Erasama, Kendrapara areas respectively. Similarly well density could be restricted upto 1-2 numbers per square kilometer along the coast line. Smaller horse power pumps with 1-3 hp could be effectively used continuously for 4/5 hours in order to avoid saline intrusion in these areas.